TESTS OF CONTROL LESSONS AS A TYPE OF MODULAR TECHNOLOGY THAT PROVIDES MONITORING OF STUDENTS’ ACADEMIC PROGRESS - Yunusova , Gulnoza Abduxalikovna (Educational Research in Universal Sciences, 2023)
The principles of modular learning impose serious features on the main types of lessons, significantly changing their tasks and course compared to traditional ones. One main type of lesson within the framework of modular technology are control lessons. Usually there are two control lessons inside the module (for organizing input and output control), sometimes there is a need for additional lessons that test the current knowledge and skills of students.